Cytotoxic evaluation of Leptospermum javanicum and Baeckea frutescens along with the anti-cancer activities of the active isolate, betulinic acid / Suerialoasan Navanesan - Suerialoasan , Navanesan (2018)
The usage of natural products as precursors for pharmacologically significant outputs has longed yielded positive outcomes. Along these lines, this study chose to look into Leptospermum javanicum and Baeckea frutescens, both found in mountainous region in Peninsular Malaysia and have limited biological investigations. The aim of the present study was to assess the cytotoxicity of both plants against lung cancer cells, followed by evaluating the anti-cancer and anti-metastatic properties of the active extracts and their compound. In addition to this, the protein expression of the active compound was evaluated to obtain a better understanding into the mechanism of action. The crude methanol extracts of both plants showed no signs of acute oral toxicity when tested on Sprague-Dawley rats. The cytotoxic potentials of the extraction yields (methanol, hexane, ethyl acetate and water extracts as wells as a semi pure fraction, LF1 from L. javanicum) were evaluated against two human non-small cell lung carcinoma cell lines (A549 and NCI-H1299) using the MTT assay, with LF1 being the most promising. LF1 treatment resulted in the manifestation of a sub-G1 region in the cell cycle analysis while also causing presences of apoptotic morphologies in cells stained with acridine orange and ethidium bromide (AO/EB). Treatment with LF1 resulted in an apoptotic population in cells that were evaluated using the Annexin V/ propidium iodide assay. Blockage of cell cycle progression was also observed in LF1-treated cells. Following this, LF1 underwent isolation and purification to yield a white powder which was identified as Betulinic acid (BA) via NMR, LCMS and IR spectroscopy. The isolate, BA, which produced an encouraging cytotoxic effect against A549 and NCI-H1299 cells through the MTT assay, was further assessed with AO/EB staining, TUNEL assay, sub-G1 population quantification as well as activated caspase-3 detection. The data pointed towards the induction of apoptosis as a result of increasing concentrations of BA, regardless of the p53 status in both cell lines. Treatment with BA also prevented an effective attachment of the invasive A549 cells onto a new culture surface, in addition to diminishing the migratory and invasive potential of treated cells across an uncoated porous membrane and a Matrigel-coated membrane, respectively. Further investigation through the ELISA detection method and gelatin zymography showed an adverse effect to production of matrix metalloproteinase-2 (MMP-2). Protein expression of BA-treated cells showed decreased levels of p-Akt, ERK1/2 and cyclin D1 followed by a slight increase in p21 and p27 expression, all of which is believed to have contributed to the G0/G1 arrest. In addition to this, alteration in NF-κB, IκB-α, STAT3 and JNK phosphorylation due to treatment with BA could have been a contributing factor to its apoptotic and anti-metastatic properties. Taken together, the results showed that the L. javanicum isolate, BA, possess anti-cancer effects through induction of apoptosis, restriction of cell cycle progression and anti-metastatic effects on human lung cancer cells. The ability of BA to not only eradicate but control the spread of lung cancer cells makes it a promising lead compound in the treatment of lung cancer.